A home of your own : creating interiors with characters - Coulthard, Sally (London : Merrell, 2013)
"An inspirational guide to introducing character into your home, full of ideas and tips on how to create a personality-packed space that reflects who you are and how you live"--Page 4 of cover.
Bumps, bangs and scratches -- Living with love -- Making your mark -- Bringing the outside in -- The devil's in the detail -- A sense of surprise.
Includes index.
Includes bibliographical references (page 185) and index.
Keywords: Interior decoration; Interior decoration -- Pictorial works